PERFORMANCE OF ACID-ADAPTIVE SOYBEAN EXPECTED LINES IN SOUTH LAMPUNG, INDONESIA - Kuswantoro, Heru; Indriani, Febria Cahya; Patriawaty, Nia Romania; Sulistyo, Apri; Han, Won Young; Lee, Poong Yeon; Cho, Yang Hee; Baek, In Youl (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Acid soil area is one of the areas broadly available in Indonesia. However, the complexity of acid soil may lead to low soybean productivity. Hence, soybean variety which is adaptive to acid soil is needed. The objective of this research was to find out expected lines adaptive to acid soil. A number of ten soybean lines and two check varieties were grown in Natar Research Station in dry season II, 2011. This research applied randomized completely block design with four replications. Results showed that 7 of 10 soybean lines had grain yield higher than those of two check varieties. The three lines with the highest grain yield were Tgm/Anj-957, Tgm/Anj-908 and Tgm/Anj-932 with grain yield 1.83, 1.74, and 1.65 t ha-,1 respectively. Tanggamus variety had grain yield higher than Wilis. The highest grain yield line, Tgm/Anj-957, was also supported by the highest number of pods per plant up to 68 pod. Line of Tgm/Anj-995 was the line with the largest seed size, i.e. 16 g per 100 seeds.Keywords: acid soil, expected lines, Glycine max, yield